Spatially Restricted Hypopigmentation Associated with an Ednrbs -Modifying Locus on Mouse Chromosome 10 - Rhim, Hyangshuk; Dunn, Karen J.; Aronzon, Anna; Mac, Susanna; Cheng, Mickie; Lamoreux, M. Lynn; Tilghman, Shirley M.; Pavan, William J.

(untitled) (Genome Research, 2000)
We have used the varied expressivity of white spotting (hypopigmentation) observed in intrasubspecific crosses ofEdnrbs mice (MayerEdnrbs/Ednrbs and C3HeB/FeJEdnrbs/Ednrbs ) to analyze the effects of modifier loci on the patterning of hypopigmentation. We have confirmed that an Ednrbs modifier locus is present on mouse Chromosome 10. This locus is now termed k10, using the nomenclature established by Dunn in 1920. Thek10Mayer allele is a recessive modifier that accounts for almost all of the genetic variance of dorsal hypopigmentation. Using intercross analyses we identified a second allele of this locus or a closely linked gene termedk10C3H . The k10C3H allele is semidominant and is associated with the penetrance and expressivity of a white forelock phenotype similar to that seen in Waardenburg syndrome. Molecular linkage analysis was used to determine that thek10 critical interval was flanked by D10Mit10 andD10Mit162/D10Mit122 and cosegregates with mast cell growth factor (Mgf). Complementation crosses with aMgfSl allele (a 3–5-cM deletion) confirm the semidominant white forelock feature of the k10C3H allele and the dorsal spotting feature of K10Mayer allele. MgF was assessed as a candidate gene fork10Mayer and k10C3H by sequence and genomic analyses. No molecular differences were observed between the Mayer and C57BL/6J alleles of MgF; however, extensive genomic differences were observed between the C3HeB/FeJ and C57BL/6J alleles. This suggests that alteration of MgF expression in C3H mice may account for the k10C3H action on white forelock hypopigmentation. Crosses of Ednrbs withKitWJ-2 (the receptor for MGF)-deficient mice confirmed the hypothesis that synergistic interaction between the Endothelin and MGF signaling pathways regulates proper neural crest-derived melanocyte development in vivo.